Oncologic outcomes among Black and White men with grade group 4 or 5 (Gleason score 8‐10) prostate cancer treated primarily by radical prostatectomy. Issue 9 (15th March 2021) - Wilkins, Lamont J.; Tosoian, Jeffrey J.; Reichard, Chad A.; Sundi, Debasish; Ranasinghe, Weranja; Alam, Ridwan; Schwen, Zeyad; Reddy, Chandana; Allaf, Mohammed; Davis, John W.; Chapin, Brian F.; Ross, Ashley E.; et al.
Abstract : Background: The aim of this study was to describe pathologic and short‐term oncologic outcomes among Black and White men with grade group 4 or 5 prostate cancer managed primarily by radical prostatectomy. Methods: This was a multi‐institutional, observational study (2005‐2015) evaluating radical prostatectomy outcomes by self‐identified race. Descriptive analysis was performed via nonparametric statistical testing to compare baseline clinicopathologic data. Univariable and multivariable time‐to‐event analyses were performed to assess biochemical recurrence (BCR), metastasis, cancer‐specific mortality (CSM), and overall survival between Black and White men. Results: In total, 1662 men were identified with grade group 4 or 5 prostate cancer initially managed by radical prostatectomy. Black men represented 11.3% of the cohort (n = 188). Black men were younger, demonstrated a longer time from diagnosis to surgery, and were at a lower clinical stage (all P  < .05). Black men had lower rates of pT3/4 disease (49.5% vs 63.5%; P  < .05) but higher rates of positive surgical margins (31.6% vs 26.5%; P  = .14) on pathologic evaluation. There was no difference in BCR, CSM, or overall survival over a median follow‐up of 40.7 months. Black men had a lower 5‐year cumulative incidence of metastasis‐free survival (93.6%; 95% confidence interval [CI], 86.5%‐97.0%) in comparison with White men (85.8%; 95% CI, 83.1%‐88.0%), which did not persist in an age‐adjusted analysis. Conclusions: Black and White men with high‐grade prostate cancer at diagnosis demonstrated similar oncologic outcomes when they were managed by primary radical prostatectomy. Our findings suggest that racial disparities in prostate cancer mortality are not related to differences in the efficacy of extirpative therapy. Abstract : Black and White men with high‐grade prostate cancer at diagnosis demonstrate similar oncologic outcomes when they are managed by primary radical prostatectomy. This study's findings suggest that racial disparities in prostate cancer mortality are not related to differences in the efficacy of extirpative therapy.